MAKIAN DALAM NOVEL AKU TAK MEMBENCI HUJAN KARYA SRI PUJI HARTINI: PERSPEKTIF PSIKOLINGUISTIK - Istifadah; Helyati; Nuril Musrifah; Mas’odi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research focuses on exploring the use of swearing in the novel “Aku Tak Membenci Hujan” through a psycholinguistic perspective. In literary works, swearing often serves as a reflection of the characters' emotions, internal struggles, and psychological states. A psycholinguistic framework is utilized to analyze how swearing manifests in the interactions between characters and how individual psychological factors influence the use of offensive or negative language. The study identifies various forms of swearing within the novel and investigates the meanings and psychological roles behind them. Data is gathered using discourse analysis techniques, with particular attention to the characters, contexts, and emotional effects conveyed through swearing. The results of the study reveal that swearing reflects the characters' feelings of frustration, anger, and dissatisfaction with both their social and personal circumstances. This analysis demonstrates that swearing is not merely a negative expression but also a window into the deeper psychological dynamics at play in the characters' development. The study offers valuable insights into the connections between language, psychology, and literature.